La inflación en el sector de la construcción VIS y el papel de la contabilidad financiera para la toma de decisiones en periodos de crisis. (2023)
The present work seeks to carry out an investigation on how inflation directly influences organizations, especially microenterprises in the social interest housing construction sector (VIS), which will be the subject of the analysis. It will be demonstrated through the qualitative method, the relevance of financial accounting and the way that this tool helps organizations to know correctly and in advance, information that will be useful when carrying out their financial and operational planning, since it allows to carry out a control of the operations carried out with our suppliers and clients, in addition to knowing at any time the situation of the company, the expenses, the costs, the level of indebtedness, the provision for taxes and profits of the business among others, in order to make the best decisions and help strengthen organizations while being certain of their operation. With quantitative and qualitative results, a relationship of sections of the investigation is established: general considerations of the economic environment and globalization, National Economy and inflation, News of the Construction of social interest housing in Colombia, Financial accounting, Decision making